GE_GERICHTE P/15278/2013 vom 15. Oktober 2018 - GE Cour de justice (2018)
VIOLENCE CONTRE LES AUTORITÉS ; ATTÉNUATION DE LA PEINE | CP.285.al1.ch1; CPP.9; CPP.325.al1; CP.48.letb; CP.48.letc; CP.48.lete; CP.52; CP.47.al2; CP.54